Circular economy policy-related national initiatives in Visegrad countries - Pomázi, István; Szabó, Elemér (European Spatial Research and Policy, 2020)
The concept of circular economy (CE) has become popular in the last decade: both decision-makers and businesses are looking for alternative solutions replacing the present economic model. Official governmental documents have been selected for introducing Visegrad countries’ (V4) initiatives and monitoring the progress toward a transition to a circular economy. Based on selected material flow and resource productivity (RP) indicators, the study compares the regional differences among Visegrad countries. The current performances of the V4 in the implementation of the circular economic model are below the EU average. Moreover, it is noticeable that the dynamics of the changes of each indicator is more positive than on average in the EU, however, only moderate relative decoupling of domestic material (DMC) from GDP has occurred. When comparing individual countries, the wide range of the policy measures taken by V4 countries to support the transition to a circular economy can be considered promising. Despite the different characteristics of Visegrad countries, they show similar performances that are rather close to each other and incrementally approach to the EU average.